2022
DOI: 10.1177/07482337221076587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BPA effects on autophagy in Neuro-2a cells

Abstract: Bisphenol A (BPA), which is used for the industrial production of polycarbonate plastics and epoxy resins, is found in many commercially available products. Plasticizer BPA produces chemical substances worldwide, and knowledge of its effects on humans and animals is increasing. In the present work, the morphology of cells was observed by optical microscopy and phalloidin staining to evaluate the toxic effect of BPA on Neuro-2a cells. Autophagy has an important role in the regulation of cell metabolism. To stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These associations suggest that decreased autophagy in the HF + BP group may be linked to changes in the eIF2α/ATF4 pathway [13]. In a previous study using Neuro-2a cells, autophagy was decreased by BPA, as determined by the reduction in beclin-1 and LC3-II/LC3-I levels, suggesting BPA-induced neurotoxicity [38]. A macrophage study also showed a BPA-induced reduction in LC3-II/LC3-I levels and an increase in p62 levels, contributing to BPA-induced immune cell injury [39].…”
Section: Discussionmentioning
confidence: 78%
“…These associations suggest that decreased autophagy in the HF + BP group may be linked to changes in the eIF2α/ATF4 pathway [13]. In a previous study using Neuro-2a cells, autophagy was decreased by BPA, as determined by the reduction in beclin-1 and LC3-II/LC3-I levels, suggesting BPA-induced neurotoxicity [38]. A macrophage study also showed a BPA-induced reduction in LC3-II/LC3-I levels and an increase in p62 levels, contributing to BPA-induced immune cell injury [39].…”
Section: Discussionmentioning
confidence: 78%
“…In a previous study using Neuro-2a cells, autophagy was decreased by BPA, as determined by the reduction in beclin-1 and LC3-II/LC3-I levels, suggesting BPA-induced neurotoxicity (Li et al 2022). A macrophage study also showed a BPA-induced reduction in LC3-II/LC3-I levels and an increase in p62 levels, contributing to BPA-induced immune cell injury (Wu et al 2022).…”
Section: Discussionmentioning
confidence: 90%